Clinical Outcomes in Duchenne Muscular Dystrophy: A Study of 5345 Patients from the TREAT-NMD DMD Global Database - Koeks, Zaïda; Bladen, Catherine L; Salgado, David; van Zwet, Erik; Pogoryelova, Oksana; McMacken, Grace; Monges, Soledad; Foncuberta, Maria E; Kekou, Kyriaki; Kosma, Konstantina; Dawkins, Hugh; Lamont, Leanne; et al. (Journal of neuromuscular diseases, 2017)
BACKGROUND: Recent short-term clinical trials in patients with Duchenne Muscular Dystrophy (DMD) have indicated greater disease variability in terms of progression than expected. In addition, as average life-expectancy increases, reliable data is required on clinical progression in the older DMD population. OBJECTIVE: To determine the effects of corticosteroids on major clinical outcomes of DMD in a large multinational cohort of genetically confirmed DMD patients. METHODS: In this cross-sectional study we analysed clinical data from 5345 genetically confirmed DMD patients from 31 countries held within the TREAT-NMD global DMD database. For analysis patients were categorised by corticosteroid background and further stratified by age. RESULTS: Loss of ambulation in non-steroid treated patients was 10 years and in corticosteroid treated patients 13 years old (p = 0.0001). Corticosteroid treated patients were less likely to need scoliosis surgery (p < 0.001) or ventilatory support (p < 0.001) and there was a mild cardioprotective effect of corticosteroids in the patient population aged 20 years and older (p = 0.0035). Patients with a single deletion of exon 45 showed an increased survival in contrast to other single exon deletions. CONCLUSIONS: This study provides data on clinical outcomes of DMD across many healthcare settings and including a sizeable cohort of older patients. Our data confirm the benefits of corticosteroid treatment on ambulation, need for scoliosis surgery, ventilation and, to a lesser extent, cardiomyopathy. This study underlines the importance of data collection via patient registries and the critical role of multi-centre collaboration in the rare disease field.
Keywords: dospělí; Muscular Dystrophy, Duchenne; Databases as Topic; Infant; předškolní dítě; dítě; novorozenec; databáze jako téma; Adult; výsledek terapie; mladý dospělý; Duchenne muscular dystrophy; průřezové studie; Adolescent; lidé; Infant, Newborn; Treatment Outcome; Adrenal Cortex Hormones; hormony kůry nadledvin; Cross-Sectional Studies; Male; kojenec; Duchennova muskulární dystrofie; TREAT-NMD; Child, Preschool; Young Adult; Child; mužské pohlaví; Neuromuscular diseases; DMD; mladiství; Humans